(untitled) (KYAMC Journal, 2017)
Increasing resistance among urinary tract pathogens to conventional drugs is found alarming worldwide. The aim of this study was to obtain data on susceptibility patterns of isolated uropathogens from urine samples of patients attending at Khwaja Yunus Ali Medical College Hospital, Enayetpur, Sirajgonj, Bangladesh a tertiary health care center of remote area to currently used antimicrobial agents. A total of 656 urine samples were studied of which 163 (24.8%) were culture positive. Among 163 culture positive cases all uropathogenic isolates were identified. Among the isolates, E. coli was the most predominant 116 (71.1%) followed by Pseudomonas aeruginosa 29 (17.8%). Staphylococcus saprophyticus 12 (7.4%) and Klebsiella pneumoniae 4 (2.4%) and Acenatobacter sp. 2 (1.2%). The majority of isolated E. coli were sensitive to Meropenam (58.6%) and Amikacin (57.7%) followed by gentamicin (52.6%), amoxiclav (43.1%), ciprofloxacin (42.2%). Sensitivity & resistance rate in Staphylococcus saprophyticus were same (50%) in Cephradine . Where complete (100%) resistanc e was shown to Ampicillin in Pseudomona s aeruginosa , Klebsiella pneumoniae and Acenatobacter sp. However most of isolates were poorly sensitive to ampicillin (1.7%), erythromycin (2.5%), cefuroxin (3.4%) and amoxicillin (9.5%). This area-specific monitoring studies aimed to gain knowledge about the type of pathogens responsible for UTIs and their resistance patterns may help the clinician to choose the right empirical treatment. Meropenem, amoxiclav, amikacin, gentamicin, second-generation of both cephalosporins and quinilones are found the most sensitive against the common uropathogens which might be used in the treatment of UTI. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 610-613